Evaluation of organ weights and ventricular thicknesses in electrocution related deaths based on autopsy reports: a biophysical approach - Kilinc, Evren; Ozturk, Onur; Oruc, Mucahit; Celbis, Osman (Journal of the Pakistan Medical Association, 2022)
Objective: To evaluate autopsy reports of the deaths due to electrocution in terms of body mass index, body surface area, and organ weights with a biophysical perspective. Method: The retrospective study was conducted in Malatya, Turkey, and comprised autopsy reports of electrocution cases that were obtained from the local branch of the Council of Forensic Medicine related to the period from 2012 to 2019. Organ weights and ventricular thicknesses were compared in terms of body mass index and body surface area. Electrical marks were also evaluated in detail. Data was analysed using SPSS 18. Results: Of the 45 cases, 36(%) were male and 9(%) were female. The overall mean age was mean age of 39±13 years (range: 20-71 years). There were no significant differences in organ weights and ventricular thicknesses in different body mass index groups (p>0.05). The weights of head and heart were significantly different in relation to body surface area (p<0.05), but no significant difference were found for other organs and ventricular thickness (p>0.05). Conclusion: Comparing the organ weights in electrocution autopsies to normal organ weights may help decide the cause of death. During autopsy, electrical marks should be evaluated by considering the characteristics of the electrical current. Key Words: Electrocution, BMI, BSA, Organ weights.